85 Is There An Association Between Tendinopathy And Diabetes Mellitus? A Systematic Review. (5th September 2014) - Ranger, Tom A; Wong, Andrea MY; Cook, Jill L; Gaida, Jamie E
Abstract : Introduction: An association between tendinopathy and diabetes mellitus (DM) has been noted across multiple studies; see review by. 1 This review aimed to identify and synthesise all available data on this topic. Methods: Nine databases were comprehensively searched for English language journal articles reporting both a tendon and diabetes related variable. Reference lists and citation tracking were used to increase the sensitivity of the search. Articles were excluded if they were: case reports, conference proceedings, animal studies or if they lacked a control group. Results: The search yielded 680 papers of which 33 were included in the final review. Meta-analysis of 4 studies identified a greater prevalence of diabetes in people with tendinopathy (OR 1.37, CI 1.05, 1.80, Figure 1 ). Similarly, meta-analysis of 12 studies identified an increased prevalence of tendinopathy in people with DM compared to controls (OR 4.93, CI 2.93, 5.55, Figure 2 ). Meta-analysis of 8 studies showed that individuals who had both tendinopathy and DM had a longer duration of disease than those who had diabetes but not tendinopathy (eight studies, mean difference: 4.75 yrs, CI 3.45, 6.05, Figure 3 ). Discussion: The findings of this review suggest that tendinopathy should be considered in management of diabetes, particularly as duration of disease increases. This is clinically relevant as unmanaged tendinopathy can limit exercise capacity, which is an accessible means of glycaemic control in diabetes. 2 In addition, management of tendinopathy can include exercise therapy to reduce pain and induce healing. 3 Exercise therefore represents a mutually beneficial intervention for people suffering from DM and tendinopathy. References: Abate, et al . Rheum . 2013;53:599–608 Boulé, et al. J Am Med As . 2001;286:121–1227 Cook, Purdham. Br J Sp Med . 2009;43:409–416